Development of rhetorical competence in Hebrew-speaking children's argumentative writing: discourse stance across grades 2–5 - Stavans, Anat; Zadunaisky-Ehrlich, Sara (Frontiers in Language Sciences, 2025)
This study investigates the development of rhetorical competence in Hebrew-speaking elementary students' argumentative writing through their use of discourse stance (DS). DS was analyzed across three dimensions each containing three characterizing categories (i.e., for (orientation dimension the categories: writer, text, audience; for attitude dimension: epistemic, deontic, emotional, and for generality dimension: personal, impersonal and generic). Participants (N = 293) in 2nd grade (age range 7 to 8 years), 3rd grade (ages 8–9), 4th grade (ages 9–10) and 5th grade (ages 10–11) wrote an argumentative essay on a familiar topic. Texts were segmented at the clause level and coded for DS categories; analyses addressed grade differences in dimension use (research question 1), developmental trajectories of categories (research question 2), and within-grade co-occurrence patterns (research question 3). Results show uneven pathways. Orientation and generality increased with grade, whereas attitude was relatively stable. Category-level patterns shifted from reliance on writer orientation, emotional stance, and personal generality in younger students to text orientation, epistemic stance, and generic generality in older students. Association analyses revealed that stance resources clustered into coherent profiles that reorganized developmentally: Grade 2 texts centered on a writer-personal-emotional bundle, whereas Grade 5 texts consolidated a text-generic-epistemic profile, with Grades 3–4 as a transitional phase. Across grades, audience orientation was rare. These findings provide one of the first systematic accounts of DS development in Hebrew children's writing and extend cross-linguistic evidence on early academic literacy. They indicate that rhetorical competence develops not only via increased use of individual stance resources but also through their reorganization into coherent stance profiles, underscoring the value of instruction that fosters generic formulations, epistemic reasoning, and audience awareness.